Students’ perceptions of mathematics teacher support on assigned homework during school breaks - Florence Kyaruzi; Innocent B. Rugambuka (Intelektual Pustaka Media Utama, 2026)
Homework is a crucial formative assessment tool that helps to keep students engaged on tasks beyond school hours. This study investigated students’ perceptions of teacher support on homework tasks during school breaks. Specifically, it focused on how students perceived the mathematics teachers’ support in terms of task quality, feedback quality, and promoting mathematics autonomy. The study also focused on how these perceptions varied by gender and school ownership type, and how they related to students’ self-efficacy in mathematics. It was carried out in Dar es Salaam, Tanzania, and involved a random sample of 579 students from six primary schools. Previously validated questionnaire scales were adapted for data collection. The data were analysed by using descriptive statistics, latent mean analyses, and structural equation modelling techniques. Results from the descriptive statistics indicated that students positively evaluated teacher support in homework. Besides, student perceptions did not significantly differ across genders but differed between school ownership. The findings indicate a significant relationship between students’ perceptions of teacher support and their mathematics self-efficacy. The findings call for the effective utilisation of homework to augment classroom instructions.